2006
DOI: 10.1038/sj.bmt.1705358
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of mesenchymal stem cells from G-CSF-mobilized human peripheral blood using fibrin microbeads

Abstract: Adult mesenchymal stem cells (MSC) that are able to differentiate into various mesenchymal cell types are typically isolated from bone marrow, but their significant presence in human peripheral blood (PB) is controversial. Fibrin microbeads (FMB) that bind matrix-dependent cells were used to isolate MSC from the mononuclear fraction of mobilized PB of adult healthy human donors treated with a granulocyte colony-stimulating factor. Isolation by plastic adherence resulted in a negligible number of MSC in all sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
170
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(179 citation statements)
references
References 35 publications
4
170
1
4
Order By: Relevance
“…8 It is worth noting that in few studies, the culture of PB-MSCs has been only occasionally achieved and not always replicable. 23 On the contrary, other studies have demonstrated that MSCs can be isolated from PB repeatedly, however their limitations remains in the low numbers of cells obtained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 It is worth noting that in few studies, the culture of PB-MSCs has been only occasionally achieved and not always replicable. 23 On the contrary, other studies have demonstrated that MSCs can be isolated from PB repeatedly, however their limitations remains in the low numbers of cells obtained.…”
Section: Discussionmentioning
confidence: 99%
“…This involves the hyper stimulation of BM production using granulocyte colony-stimulating factor (G-CSF). 8 This, however, results in the production of immature progenitor cells, for example, blasts, rather than the true multipotential MSCs. 11 In addition, it has also been demonstrated that this technique does not selectively produce MSCs but rather a mix of MSCs, hematopoietic stem cells and, other immature progenitor cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…32 Desde então, inúmeros relatos têm surgido na literatura demonstrando a presença, no sangue periférico, de células com capacidade de se diferenciarem em outras células no tecido conjuntivo. [33][34][35][36][37][38] Tondreau e col. 34 testaram o potencial do sangue periférico mobilizado com fator de crescimento como fonte de células-tronco mesenquimais. Os autores demonstraram que CTM podem ser facilmente isoladas a partir da fração de células CD133+ do sangue périférico mobilizado.…”
Section: Sangue Periférico Como Fonte De Células-tronco Mesenquimaisunclassified
“…37,38 Another type of multipotent stem cells are the MSCs which have the capacity to develop into functional cells of the mesenchymal lineage e.g., osteocytes, chondrocytes and adipocytes. 46,47 As MSCs can be found in both BM and PBSC 48,49 it could be speculated that these cells may constitute "adipogenic" BMDCs. Based on data from murine models, additional cell sources could be endothelial cells.…”
mentioning
confidence: 99%